2018
DOI: 10.1155/2018/1913848
|View full text |Cite
|
Sign up to set email alerts
|

The Migration and Transformation of Heavy Metals in Sewage Sludge during Hydrothermal Carbonization Combined with Combustion

Abstract: The migration and transformation behaviors of heavy metals (HMs), including Cr, Mn, Ni, Cu, Zn, As, Cd, and Pb, during the hydrothermal carbonization (HTC) of sewage sludge (SS) were investigated. The immobilization of HMs during the combustion of solid residual (SR) produced from HTC of SS was also analyzed. With increasing HTC temperature and residence time, the majority of HMs (except As) accumulated in the SR. The residual rate of As in the SR decreased from 73.95% to 56.74% when the residence time was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…In contrast, the species of heavy metals converted from unstable to stable with the increase in temperature. Numerous studies demonstrated that the acid-soluble/exchangeable and reducible fraction of heavy metals could transform into oxidizable and residual fractions through complexation during hydrothermal conversion [21,[40][41][42][43]. A possible explanation for the stabilization of heavy metals during HTC is that the unstable adsorbed or dissolved heavy metals (F1 + F2) were entrapped by the organic matter with a complex structure to form stable phases and fixation in the hydrochars, and the higher the HTC temperature, the stronger the effect.…”
Section: The Effect Of Temperature and Hcl Addition On Heavy Metal Di...mentioning
confidence: 99%
“…In contrast, the species of heavy metals converted from unstable to stable with the increase in temperature. Numerous studies demonstrated that the acid-soluble/exchangeable and reducible fraction of heavy metals could transform into oxidizable and residual fractions through complexation during hydrothermal conversion [21,[40][41][42][43]. A possible explanation for the stabilization of heavy metals during HTC is that the unstable adsorbed or dissolved heavy metals (F1 + F2) were entrapped by the organic matter with a complex structure to form stable phases and fixation in the hydrochars, and the higher the HTC temperature, the stronger the effect.…”
Section: The Effect Of Temperature and Hcl Addition On Heavy Metal Di...mentioning
confidence: 99%
“…Elemental analysis confirmed that most HM stayed in the hydrochar. An explanation for the high selectivity is the sorption property of the char [22] and the reduction of HM solubility after the HTC-treatment [40].…”
Section: Nutrient Recoverymentioning
confidence: 99%
“…Similarly, HT alone can significantly affect metal speciation in sewage sludge. , Our recent study revealed that the transformation of Cu and Zn in sewage sludge during HT was highly dependent on treatment temperature . Cr exists predominantly as an organo-Cr­(III) complex in activated sludge, , and HT can convert bioavailable Cr fractions into more stable fractions , as oxidizable and residual fractions in HT hydrochars. , A recent study reported that HT under alkaline conditions favors the immobilization of Cr, while it is the opposite under acidic conditions . To the best of our knowledge, no study has systematically investigated Cu, Zn, and Cr speciation evolution in sewage sludge during combined HT/AD.…”
Section: Introductionmentioning
confidence: 99%
“…15,20 Our recent study revealed that the transformation of Cu and Zn in sewage sludge during HT was highly dependent on treatment temperature. 15 Cr exists predominantly as an organo-Cr(III) complex in activated sludge, 21,22 and HT can convert bioavailable Cr fractions into more stable fractions 23,24 as oxidizable and residual fractions in HT hydrochars. 20,25 A recent study reported that HT under alkaline conditions favors the immobilization of Cr, while it is the opposite under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%